MAVEN insights into oxygen pickup ions at Mars. Issue 21 (5th November 2015) - Rahmati, A.; Larson, D. E.; Cravens, T. E.; Lillis, R. J.; Dunn, P. A.; Halekas, J. S.; Connerney, J. E.; Eparvier, F. G.; Thiemann, E. M. B.; Jakosky, B. M.
Abstract: Since Mars Atmosphere and Volatile EvolutioN (MAVEN)'s arrival at Mars on 21 September 2014, the SEP (Solar Energetic Particle) instrument on board the MAVEN spacecraft has been detecting oxygen pickup ions with energies of a few tens of keV up to 200 keV. These ions are created in the distant upstream part of the hot atomic oxygen exosphere of Mars, via photoionization, charge exchange with solar wind protons, and electron impact. Once ionized, atomic oxygen ions are picked up by the solar wind and accelerated downstream, reaching energies high enough for SEP to detect them. We model the flux of oxygen pickup ions observed by MAVEN SEP in the undisturbed upstream solar wind and compare our results with SEP's measurements. Model‐data comparisons of SEP fluxes confirm that pickup oxygen associated with the Martian exospheric hot oxygen is indeed responsible for the MAVEN SEP observations. Key Points: Oxygen pickup ions are detected by MAVEN SEP in the undisturbed solar wind at Mars Model‐data comparisons indicate pickup oxygen associated with the Martian exospheric hot oxygen Statistical analysis of SEP data constrains exospheric hot oxygen densities and escape at Mars